Quantification of Particle Filtration Using a Quartz Crystal Microbalance Embedded in a Microfluidic Channel - Ji, Siqi (Langmuir : the ACS journal of surfaces and colloids, 2023)
To quantify colloidal filtration, a quartz crystal microbalance (QCM) with a silicon dioxide surface is embedded on the inner surface of a microfluidic channel to monitor the real-time particle deposition. Potassium chloride solution with micrometer-size polystyrene particles simulating bacterial strains flows down the channel. In the presence of intrinsic Derjaguin-Landau-Verwey-Overbeek (DLVO) intersurface forces, particles are trapped by the quartz surfaces, and the increased mass shifts the QCM resonance frequency. The method provides an alternative way to measure filtration efficiency in an optically opaque channel and its dependence on the ionic concentration